Application of modified TOPSIS technique in deciding optimal combination for bio-degradable composite. (November 2018) - Jha, Kanishka; Kumar, Ravinder; Verma, Kartikey; Chaudhary, Babulal; Tyagi, Y.K.; Singh, Subhash
Abstract: The combined fuzzy analytical hierarchy process (F-AHP) and fuzzy technique for order preference by similarity to ideal solution (F-TOPSIS) approach used to access performance defining attributes (PDAs) such as Tensile Strength, Flexural Strength, Impact Strength, Elongation at break (%), Diffusion Coefficient (D), Sorption Coefficient (S) and Permeability Coefficient (P) of fabricated biodegradable composite materials. The weight of different PDA's was evaluated by F-AHP where the PDA's are Tensile Strength, Flexural Strength Impact Strength, Elongation%, Diffusion, Sorption and Permeability. F-TOPSIS was employed to determine the optimal ranking of the composite materials as BC-1>BC-7>BC-2>BC-6>BC-5>BC-3>BC-4. The alternatives other than neat PCL, with fiber, matrix and graphite at 45, 55 & 15 wt fraction (i.e., BC-7) showed optimum results. Highlights: A novel Pine Cone reinforced biodegradable composite was developed and characterized. Comparable mechanical properties were achieved along with biodegradation of the composites. Hybrid MCDM approach was incorporated (F-AHP TOPSIS) for selecting optimal combination. F-AHP and F-TOPSIS was found to be a competent MCDM technique.